HUMAN CAPITAL DEVELOPMENT AND ECONOMIC GROWTH IN LATVIA - Romele, Linda (European Scientific Journal, ESJ, 2013)
Common opinion exists about positive relationship between human capital development and economic growth. However during last decade more people acquire higher level of education despite social economic recession. There are several methods how to measure human capital. The author chooses two methods and estimates average years of schooling during 2000 – 2010 and human capital stock. For second the Mincer rate of return is estimated which shows the average rate of return from one additional year of schooling. Finally the author uses simple production function to estimate the human capital impact on labour productivity. The author finds that women human capital has positive impact on labour productivity during the period 2000 – 2010.